2015
DOI: 10.1002/hrdq.21213
|View full text |Cite
|
Sign up to set email alerts
|

The Invisible Learning Ceiling: Informal Learning Among Preschool Teachers and Assistants in a Norwegian Kindergarten

Abstract: Individuals and society invest ever-increasing resources in formal educational programs. However, informal workplace learning may be an effective alternative source for enhancing competencies, but, unfortunately, our knowledge about informal learning is still limited. We extend the research on informal learning to the unexplored occupational group of kindergarten employees. Our research questions pertain to identifying activities that lead to informal learning, to conditions that promote or prevent such learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
0
6
0
2
Order By: Relevance
“…For example, employees working in public sectors and education, health, and social service industries participated more actively in informal learning. The structure of constituents also affected informal learning (Schei & Nerbø, 2015). In particular, hierarchical order in rank hindered informal learning and interfered with active communication (Holley et al, 2016).…”
Section: The Antecedents Of Informal Learning In the Workplacementioning
confidence: 99%
See 2 more Smart Citations
“…For example, employees working in public sectors and education, health, and social service industries participated more actively in informal learning. The structure of constituents also affected informal learning (Schei & Nerbø, 2015). In particular, hierarchical order in rank hindered informal learning and interfered with active communication (Holley et al, 2016).…”
Section: The Antecedents Of Informal Learning In the Workplacementioning
confidence: 99%
“…Especially for newcomers, mentoring, as a way of continuing professional education, was a major vehicle for self-development (Neher et al, 2015; Pifer et al, 2015; Williams, 2003). In addition, a positive and psychologically safe environment was a prominent aspect of learning culture (Schei & Nerbø, 2015; Schürmann & Beausaert, 2016). In many cases, informal learning occurred through trial and error.…”
Section: The Antecedents Of Informal Learning In the Workplacementioning
confidence: 99%
See 1 more Smart Citation
“…Empirical research in the kindergarten context identified ten different activities that contribute to professional development. Four of the ten are individual learning activities (practicing, experimenting, reflection, and reading literature), but the other six are manifested through interaction with others (discussion, asking for professional advice, observation, mentoring, critical comments, training) (Schei & Nerbo, 2015). In Jensen and Iannone's research (2018) critical reflection, communities of practice, and networking were identified as crucial aspects of kindergarten teachers' professional development in terms of innovation.…”
Section: The Most Important Characteristics Of Kindergarten Teachers' Professional Developmentmentioning
confidence: 99%
“…The teachers' continuous professional development, which is the learning process that brings along changes in their teaching practices, and therefore in the development of the children's outcomes (Darling-Hammond & Richardson, 2009), has key importance regarding the level of professional work. Although several forms of learning activities embedded in the teachers' work have been identified by empirical studies (Kwakman, 2003;Hoekstra, Beijaard, Brekelmans, & Korthagen, 2007;Kyndt, Gijbels, Groseman, & Donche, 2016;Schei & Nerbo, 2015), their formal instalment into the elements of the teachers' progress is still problematic. The research examines the effect of the implementation of the Master programmes on teachers' everyday work and professional development.…”
Section: Introductionmentioning
confidence: 99%